2006
DOI: 10.1160/th06-05-0236
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro and in-vivo consequences of mutations in the von Willebrand factor cleaving protease ADAMTS13 in thrombotic thrombocytopenic purpura

Abstract: SummaryThrombotic thrombocytopenic purpura (TTP) is a disease characterized by microvascular thrombosis, often associated with deficiency of the von Willebrand factor (VWF) cleaving protease ADAMTS13.We investigated the spectrum of ADAMTS13 gene mutations in patients with TTP and congenital ADAMTS13 deficiency to establish the consequences on ADAMTS13 processing and activity. We describe five missense (V88M, G1239V, R1060W, R1123C and R1219W), 1 nonsense (W1016Stop) and 1 insertion (82_83insT) mutations. In tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
65
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 29 publications
2
65
1
1
Order By: Relevance
“…In 24 patients [27][28][29][30][31][32][33][34][35][36], ADAMTS13 was documented (ADAMTS13 activity lower than 10% in the absence of auto-antibodies) including 15 cases in whom ADAMTS13 genotype could also be characterized (Supplementary Table 2) [30,32,34,36]. Interestingly, all 6 cases reported from the Western World [30,32,36] carried the R1060W mutation (either heterozygous or homozygous), reported to be a marker for adult TTP [32], and they were indeed associated with an adult-onset USS initially recognized with the first pregnancy (Supplementary Table 2). In contrast, the largest series of 9 pregnancy-associated USS reported in Japan by Fujimura et al [34], showed miscellaneous mutations not including the R1060W ADAMTS13 variant: interestingly, 6 of these 9 women had episodes of severe to mild thrombocytopenia during childhood that had been incorrectly diagnosed as ITP while 3 patients had an adult-onset TTP initially recognized with pregnancy.…”
Section: Specific Features Of Pregnancy-associated Ttp At Presentatiomentioning
confidence: 99%
“…In 24 patients [27][28][29][30][31][32][33][34][35][36], ADAMTS13 was documented (ADAMTS13 activity lower than 10% in the absence of auto-antibodies) including 15 cases in whom ADAMTS13 genotype could also be characterized (Supplementary Table 2) [30,32,34,36]. Interestingly, all 6 cases reported from the Western World [30,32,36] carried the R1060W mutation (either heterozygous or homozygous), reported to be a marker for adult TTP [32], and they were indeed associated with an adult-onset USS initially recognized with the first pregnancy (Supplementary Table 2). In contrast, the largest series of 9 pregnancy-associated USS reported in Japan by Fujimura et al [34], showed miscellaneous mutations not including the R1060W ADAMTS13 variant: interestingly, 6 of these 9 women had episodes of severe to mild thrombocytopenia during childhood that had been incorrectly diagnosed as ITP while 3 patients had an adult-onset TTP initially recognized with pregnancy.…”
Section: Specific Features Of Pregnancy-associated Ttp At Presentatiomentioning
confidence: 99%
“…More than 65 mutations, including nonsense, missense, frame-shifting insertion or deletion and splicing mutations, have been detected in patients with hereditary TTP [99][100][101][102][103]. The mutations affect the process of protease synthesis, activity, or more commonly, secretion.…”
Section: Hereditary Thrombotic Thrombocytopenic Purpuramentioning
confidence: 99%
“…Inherited TTP is a rare autosomal recessive disorder due to homozygous or double heterozygous mutations in the ADAMTS-13 gene, causing a severe decrease of ADAMTS-13 level and activity (10)(11)(12)(13)(14)(15)(16). About 100 mutations causing inherited ADAMTS-13 deficiency have been identified so far in regions of the gene encoding different domains (10)(11)(12)(13)(14)(15)(16)(17) with only a few of them characterized by in vitro expression studies (12,15,(18)(19)(20)(21)(22). In this manuscript, we report cases of congenital TTP, due to the homozygous mutation in ADAMTS-13 gene in two young brothers born from two consanguineous parents of Romanian origin.…”
Section: Introductionmentioning
confidence: 99%